Farming for conservation : how Eiderdown farmers’ practices and perspectives impact breeding Arctic Terns in Iceland - Morin, Eliza-Jane, 1994- (2020)
Verkefnið er lokað til 01.06.2023 Global bird populations are currently experiencing important declines which have mainly been attributed to anthropogenic activities. However, human activities can also have positive impacts on avian populations. One potential benefit is indirect protection through use of predation control by farmers. Iceland is home to one of the largest eiderdown farming industries in the world. Eiderdown farmers use several methods to protect their eider colonies including predator control. These measures may also indirectly benefit other bird species such as Arctic terns (ARTE), which are often found nesting in association with Common eiders. Additionally, farmers may receive some benefits from ARTE nesting on their farm as they may help farmers deter predators through aggressive nest defense behaviors. For these reasons, this thesis aimed to study the impacts of eider farming practices on ARTE nesting within a farm site and farmers general perceptions of ARTE. A mixed methodology approach was used to answer the research questions, this included measuring differences in breeding success, adult condition, and resource allocation in ARTE found within and outside an eider farm on the Southern Peninsula of Iceland. Additionally, a survey was used to study the socioeconomic factors of the Icelandic eiderdown industry and farmers perceptions of ARTE. Results showed that ARTE nesting outside of an eider farm laid on average 2.18 days later than those nesting within a farm. ARTE nesting outside of an eider farm also took on average 0.91 sec longer to capture than adults found nesting on an eider farm. Indirect protection of eider farming practices may improve habitat quality for ARTE nesting on a farm site through lower predation risk which may explain earlier laying dates and bolder individuals for adults nesting on an eider farm. Survey findings showed that eider farmers had positive perceptions of ARTE nesting on their farm regardless of socioeconomic background and perceived ARTE as an ...